Mengungkap Akuntabilitas Pengelolaan Dana Punia Pada Pura Dang Kahyangan Jati, Kabupaten Jembrana, Bali - Putu Mitha Aryasita; I Gede Agus Pertama Yudantara (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aimed to determine how to manage accountability of punia funds at Pura Dang Kahyangan Jati, Jembrana Regency, Bali. This research used qualitative method with descriptive research type. Sources of data used are primary and secondary data. Primary data were obtained from the results of interviews with temple administrators, stakeholders, and the community who own the Dang Kahyangan Jati Temple. Secondary data obtained from financial reports and other literature. Methods of data collection is done through observation, interviews, and documentation. The data analysis method is carried out through the process of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicated that the report on the recapitulation of income and expenditure of Pura Dang Kahyangan Jati which aims to provided information related to income and expenses that occur during a period as well as a form of accountability for the poor community. In addition, the recapitulation report will also be submitted at the pempon meeting attended by the temple management, representatives from the four pengempon villages and the priests of the Dang Kahyangan Jati Temple.